Planning and budgeting to deliver services for mental health : mental health policy and service guidance package. (World Health Organization, 2003)
The purpose of this module is to present a clear and rational planning model for assessing the needs of local populations for mental health care and planning services. The module includes detailed technical information to assist planners to assess their current mental health services, use epidemiological data to calculate the resources required for mental health care, set budgeting and planning targets and implement those targets. Using practical examples to illustrate the calculations throughout, the module aims to provide countries with a set of planning and budgeting tools to assist with th.